Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/hsr2.960
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge, attitude, and practice (KAP) towards physical activity (PA) and its impact on obesity management in Bangladesh: A cross‐sectional study

Abstract: Background and Aims The purpose of this study was to evaluate the Bangladeshi people's current knowledge, attitude, and practice (KAP) on obesity and physical activity (PA), as well as the associated factors. Methods The KAP was evaluated using a standard questionnaire among 429 individuals, of whom 75.5% were men and had a mean age (±SD) of 28.9 ± 7.9 years. Using a mobile‐based KoBo toolbox v.25.0 program, information was gathered from respondents who resided in various districts. A Chi‐square test and a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This is also is congruent with the consistency in the attitude and value system of the individuals and their behaviors toward PA that have frequently has been addressed in other studies. 74,75 Similarly, as found in the known-group validity, male and female university students reported different tendencies to avoid PA and sport. Several studies have already reported that (compared to males) females may less be motivated to engage in PA due to their concerns regarding body image or physical appearance.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…This is also is congruent with the consistency in the attitude and value system of the individuals and their behaviors toward PA that have frequently has been addressed in other studies. 74,75 Similarly, as found in the known-group validity, male and female university students reported different tendencies to avoid PA and sport. Several studies have already reported that (compared to males) females may less be motivated to engage in PA due to their concerns regarding body image or physical appearance.…”
mentioning
confidence: 57%
“…This is also is congruent with the consistency in the attitude and value system of the individuals and their behaviors toward PA that have frequently has been addressed in other studies. 74 , 75 …”
Section: Discussionmentioning
confidence: 99%
“…Still, a meta-analysis of 13 randomized clinical trials showed that the application of the implementation intentions strategy to promote physical activity was capable of increasing physical activity practice [ 22 ]. Moreover, a positive attitude towards physical activity was shown in previous studies to be inversely associated with obesity [ 23 ] and smoking [ 24 ].…”
Section: Discussionmentioning
confidence: 98%
“…Training and a solid legal framework were suggested to enhance AI adoption in healthcare. Moreover, AI perception among Iranian healthcare workers was investigated (Hamedani et al., 2023). This Iranian study evaluated physicians and nurses' knowledge, attitudes, and acceptance of AI.…”
Section: Literature Reviewmentioning
confidence: 99%